Novel Plant Growth Regulators and their Potential Uses in Agriculture - Mishra, Ankita; Panda, Debasish (International Journal of Bio-resource and Stress Management, 2017)
Phytohormones or plant growth regulators play a crucial role in plant growth and developmental process. Apart from the traditional plant hormones studied so far i.e., auxin, gibberellins, cytokinin, abscisic acid, and ethylene, various other biomolecules are being reported to act as hormones. Several novel plant growth regulators discovered in the recent past includes compounds like Melatonin, Serotonin, Strigolactone, Harzianolide and Karrikins. Melatonin and Serotonin which were previously studied exclusively due to their function as neurotransmitter in animals are also being reported in plants widely. These two hormones impart specific functions during biotic and abiotic stress as well as plant growth and developmental processes. On the other hand Strigolactone previously reported as germination stimulant for weed species, also has important function in plant architecture modification. Strigolactone also imparts resistance to plants during abiotic stresses i.e. drought, salinity, heavy metal stress, temperature, nutrient starvation as well as various biotic stresses. It can be used along with the major plant hormones- auxin and cytokinin to regulate organogenesis. Reports elucidating the nature of these newly discovered biomolecules, there effects on plant growth and developmental processes as well as their interaction with other traditional hormones and other organic and inorganic molecules keep open the door for further exploration. Harzianolide isolated from Trichoderma harzianum was studied for its role in plant growth and systemic resistance. These secondary metabolites of Trichoderma promote plant growth through better root development and activation of plant defense responses. Karrikins are a group of plant growth regulators found in the smoke of burning plant materials are known to stimulate the germination of seeds. This paper reviews the literature supporting evidence on different novel plant growth regulators and their potential roles in agriculture.